Experimental Study of an Aluminum-Polysilicon Thermopile for Implementation of Airflow Sensor on Silicon Chip - Ayub Subandi; Irman Idris; Adang Suwandi Ahmad (Journal of Engineering and Technological Sciences, 2007)
A multi-directional airflow sensor has been realized. The essential part of  the  considered  sensor  is  a  thermopile  configuration,  which  enables  the measurement  of  flow  speed  and  flow  direction.  The  thermopile  is  a  series arrangement  of  eight  thermocouples.  A  thermocouple  converts  a  difference  in temperature  into  an  electrical  signal,  by  means  of  the  Seebeck  effect .  The thermocouples  are  made  of  aluminum-N-type  polysilicon  junctions.  The incoming  flow  is  heated  and  the  degree  of  heat  transfer  by  convection  to  the flow, depends on the speed of the flow; the faster the flow the smaller the heat transfer,  which leads to a smaller (Seebeck) output  voltage of  the thermopiles. After  signal  conditioning  -  i.e.,  filtering  and  amplification  by  means  of  an amplification system  -  the electrical output signals of the thermopiles are further signal-processed by applying analog-to-digital signal conversion, so that finally the flow speed and the flow direction can be properly displayed on a computer screen. The measured values of the Seebeck coefficient or thermopower (S) were in the range of: 0.43 to 0.68 mV/K which are in good agreement with the values found in the literature: 0.5 to 0.7 mV/K. Moreover, it  was found that the  flow speed  Uï‚¥ is  proportional  to  the  reciprocal  value  of  the  square  of  the  output voltage of the outgoing thermopile.